BUDAYA GOTONG ROYONG ETNIS TORAJA DALAM MEMBANGUN RUMAH ADAT TONGKONAN DI LEMBANG BAU BULLIAN MASSA’BU, KECAMATAN SANGALLA’, KABUPATEN TANA TORAJA - Yance Rante Lembang; Maryam Lamadirisi; Hamdi Gugule (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2020)
The research objective is to analyze the application of the culture of mutual cooperation to the Toraja ethnic group in building Tongkonan traditional houses and to describe the changes in the continuation of current mutual cooperation in the Toraja people. The problem in this research is how to apply the culture of mutual cooperation in the construction of the Tongkonan traditional house. The research method used is qualitative. Qualitative research methods aim to provide a systematic, factual and accurate description. Data collection techniques are observation, interview and documentation. The results of research in the field show that the culture of mutual cooperation in Toraja society still exists and is maintained today. One of the mutual cooperation carried out is building the Tongkonan, in this development the Toraja people form a committee through family deliberations and cooperate in collecting funds from each member of the Tongkonan family. The Tongkonan construction process is carried out in accordance with customary provisions by following the procedures for building the traditional house. The traditional Tongkonan house that was built by the Toraja people has undergone a change in shape, but the meaning of the change in shape remains the same as in the traditional Tongkonan house in general.